Verissima et ivcvndissima descriptio..., de Ulrico Schmidl: literatura de viagem ou relato de viagem? - Fioreto, Thissiane [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research was conducted on philological methodology, which proceeds the study of language based on the written text. This work aims to investigate the Latin version of Schidl's travel report. It is a narrative/register about the experience a Bavarian soldier called Ulrico Schimidl had supposedly lived in a Spanish ship, commanded by the adelantado Pedro de Mendonza, to Rio da Prata area in order to explore the Southern American continent, in the XVI Century. The Bavarian soldier would have lived some years in the region and, after returning to Europe, he would have registered what he had lived during that time. This narrative would have had its first publication, in German, in 1567. After that, the narrative had been translated and published in several languages, and it would have spread and had become one of the first and most important sources for the study of the European conquer and colonization of the region, and it has been calling the attention of researchers up to the present day. After investigating the transmission history of the document, this research selected a transcription, translation and analysis of the 1599 edition of the document, published in Latin by the De Bry's family printing house and translated from the German by Gottard Arthus. Therefore, the objective of this research is to discuss and to prove that the text can be defined as a literary genre, with its own peculiar characteristics, called Travel Narrative, according to the definition of literary genre defended by Todorov and the Russian Formalism, and also by Carrizo Rueda's theoretic and methodological view, the lattest used as a reference to this paper. It is assumed that Schimidl's text has a defined literary aesthetics, what proves that it is neither a historic document nor a kind of generically denominated travel literature

Fruto de pesquisa realizada com metodologia filológica, cuja função é proceder ao estudo da língua com base no texto escrito, este trabalho debate a versão em latim do relato de viagem de Schmidl. Trata-se do registro da experiência que supostamente viveu o soldado bávaro Ulrico Schmidl em viagem à região do Rio da Prata, numa embarcação espanhola comandada pelo adelantado Pedro de Mendoza, para explorar o sul do continente americano, na primeira metade do século XVI. O soldado bávaro passou alguns anos na região e, ao regressar à Europa, registrou o que viveu neste período. Esta narrativa teve sua primeira publicação, em alemão, em 1567. Depois disso, traduzida e publicada em várias outras línguas, a narrativa difundiu-se e tornou-se uma das primeiras e principais fontes de estudos sobre a conquista e povoação europeia da região, suscitando até hoje o interesse de pesquisadores. Após uma investigação da história de transmissão do documento, optou-se pela transcrição, tradução e análise de sua edição de 1599, publicada em latim pela casa impressora da família De Bry, e traduzida do alemão por Gottard Arthus. Assim, o objetivo desta pesquisa é, além de apresentar e divulgar o documento, sobretudo, discutir e comprovar que se trata de um gênero literário, com características peculiares, denominado Relato de Viagem, segundo a proposta teórico-metodológica de Carrizo Rueda, autora que se baseia no formalismo russo e na proposta de definição de gênero literário defendida por Todorov. Acredita-se e demonstra-se, portanto, que o texto de Schmidl possui uma estética literária definida, e não é apenas um documento histórico ou uma literatura de viagem genericamente nomeada
Keywords: Narrativas pessoais; Filologia moderna; Língua latina